Review Paper on Downsizing - Mohanty, Sasmita (International Journal of Psychosocial Rehabilitation, 2019)
As the downsizing of employees has become increasingly ubiquitous in recent years, the study of this phenomenon has taken on greater importance. The paper explores an integrative structure that combines environmental and organizational contexts, as well as downsizing consequences for individuals and organizations. Core scientific studies are checked, finding important trends and inconsistencies. The incidences of downsizing activities across economies and across organizations have been growing globally. This was seen as the basis on which to deal with increased competition. The present paper is looking into some downsizing studies. The paper focuses mainly on the research methodology used in those studies. This paper analyzes the approaches used for downsizing research and proposes the optimal study methods for: a) organizational outcomes and b) individual outcomes, including victims, survivors, and implementers. The recommendation is to have context-specific and problem specific studies with greater emphasis on the triangulation of qualitative and quantitative methods in order to improve study soundness.